Management and forecast of dynamic customer needs : an immunity-based approach - Chong, Yih Tng (2010)
With rapidly growing competition intensity, globalization, and technological advancement, high volatility of consumer needs has been observed. Product developers in volatile markets face the challenge of capturing fast moving targets - customer requirements. Customer needs can vary considerably across the period between the time of requirement elicitation and market introduction of a product. The variation contributes to the uncertainties of the product’s market acceptance. Therefore, it is crucial for developers to grasp the dynamism of customers’ needs in the processes of making decisions during product development cycles, especially in markets where requirements fluctuate considerably across time. Modern technology allows companies to gather vast amount of data concerning individuals and their habits on a periodical basis. An approach to deal with the issue of fast shifting customer needs is to dynamically acquire requirement data through effective media such as the Internet. Information derived from analyzing the time-series data may therefore serve to reduce the uncertainties of success that are inherent in product development projects. This study aims to advance the body of knowledge that is necessary to address the issue of dynamic customer needs. Research in the area of dynamic customer requirements and the potential solutions to the problem are reviewed. The boundaries of the research areas are identified and a set of research problems is accordingly defined.